2006
DOI: 10.1124/dmd.106.010397
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Rat UDP-Glucuronosyltransferases in Liver and Duodenum by Microsomal Enzyme Inducers That Activate Various Transcriptional Pathways

Abstract: ABSTRACT:Microsomal enzyme inducers (MEIs) up-regulate phase I biotransformation enzymes, most notably cytochromes P450. Transcriptional up-regulation by MEIs occurs through at least three nuclear receptor mechanisms: constitutive androstane receptor (CAR; CYP2B inducers), pregnane X receptor (PXR; CYP3A inducers), and peroxisome proliferator-activated receptor ␣ (PPAR␣; CYP4A inducers). Other mechanisms include transcription factors aryl hydrocarbon receptor (AhR; CYP1A inducers), and nuclear factor erythroid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
63
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(69 citation statements)
references
References 42 publications
4
63
2
Order By: Relevance
“…However, two other AhR ligands, 3MC and bNF, did not induce 7HC conjugation via UGT1A6 (Ikushiro et al, 2004) or UGT1A7/8 (Webb et al, 2005), which is in line with reported findings that UGT1A6 -8 mRNA expression was not induced in rat duodenum after in vivo administration of bNF (Shelby and Klaassen, 2006). Dexamethasone, a known rodent PXR agonist at the concentration used, induces CYP3A in rat (Savas et al, 1999).…”
Section: Discussionsupporting
confidence: 80%
“…However, two other AhR ligands, 3MC and bNF, did not induce 7HC conjugation via UGT1A6 (Ikushiro et al, 2004) or UGT1A7/8 (Webb et al, 2005), which is in line with reported findings that UGT1A6 -8 mRNA expression was not induced in rat duodenum after in vivo administration of bNF (Shelby and Klaassen, 2006). Dexamethasone, a known rodent PXR agonist at the concentration used, induces CYP3A in rat (Savas et al, 1999).…”
Section: Discussionsupporting
confidence: 80%
“…In addition to regulation by exogenous inducers, studies with LATF-and Nrf2-deficient mice suggest that basal expression of UGTs is also controlled by the discussed LATFs (indicated by +). Rat UGT induction data are taken from [17], human estimates are described in the text. + indicates < 2-fold, ++ 2- Table Page 28 of 31 A c c e p t e d M a n u s c r i p t …”
Section: Page 13 Of 31mentioning
confidence: 99%
“…In addition, treatment of rats with fibrates led to their characterization as peroxisome proliferators [12], CYP4 family inducers [5], and identification of PPARα as the responsible LATF [13]. It was soon recognized that these inducers also differentially activated other xenobiotic-metabolizing enzymes (XMEs), for example, UGT supergene family members [14] which similar to CYPs are differentially induced in rat liver by aryl hydrocarbons, phenobarbital and fibrates [15][16][17]. Recognition of common LATF-binding response elements in the regulatory region of target genes suggests that Phase I and II XMEs, drug transporters (Phase III) as well as LATFs represent an evolutionary conserved detoxification system for lipid-soluble endo-and xenobiotics [5,11,18,19].…”
Section: Introductionmentioning
confidence: 99%
“…29) The present study focused on nuclear receptors, which have been reported to regulate the expression of UGT2B in the liver. UGT2B expression in the liver is regulated primarily by the constitutive androstane receptor (CAR), [30][31][32] a nuclear receptor and conjugating enzyme most highly expressed in the liver; this receptor is also found in the small intestine. In addition to conjugating enzymes such as UGT2B, metabolizing enzymes such as CYP2B [33][34][35] and transporters such as multidrug resistance-associated protein 2 (MRP2) 36,37) are known to be target genes of CAR.…”
mentioning
confidence: 99%